Difference between remimazolam toluenesulfonic acid and propofol in waking quality and conscious state after general anesthesia. Issue 3 (28th September 2021) - Li, Juan; Zhou, Di; Jin, Yang; Zhou, Hong‐Su; Fang, Chang‐Le; Zhu, Zhao‐Qiong; Xiong, Liu‐Lin
Abstract : Objective: To explore the difference of anesthesia recovery and postoperative conscious state between remimazolam toluenesulfonic acid and propofol after induction and maintenance of general anesthesia. Methods: 104 patients undergoing elective tracheal intubation general anesthesia in our hospital were randomly divided into 2 groups: Remimazolam Toluenesulfonic acid group (Group R) and Propofol group (Group P). MOAA/S score, the modified Aldrete score, recovery index, time point, a state of consciousness, interpretative vital signs and adverse events were monitored at different time. Results: Compared with the Group P, the extubation time and orientation recovery time of the Group R were significantly shorter. When the operation time was less than 1 hour, the MOAA/S score of the Group R was shorter than that of Group P at 5 min and 15 min after the operation. To compare with the Group P, the score of MOAA/S in the Group R increased at 5 min, 20 min and 30 min after the operation. When the operation time was less than or equal to 1 h, the modified Aldrete score in the Group R was slightly higher than that in the Group P at 30 min after extubation. There was no injection pain in the the Group R, and the incidence of hypotension was lower than that of propofol. Conclusion: Compared with Propofol, when the operation time of general anesthesia is more than 1 hour, recovery time of Remimazolam Toluenesulfonic acid is shorter, with more complete and higher‐quality recovery.